Comparative analysis of gut microbiota and metabolome in captive Chinese and Malayan pangolins - Xiang, Chengwei; Su, Luna; Han, Mingzheng; Liang, Jieren; Hou, Fanghui; Liao, Jianzhao (Frontiers in Microbiology, 2025)
As an endangered species in the world, pangolins have attracted much attention due to their unique ecological value. In captivity, pangolins face numerous survival challenges, especially intestinal health problems, which are closely related to the gut microbiome and metabolome. The aim of this study was to contrast the gut microbiota and metabolome of Chinese pangolin and Malayan pangolin in captivity, which in order to explore the differences in digestive physiology and metabolic function between the two species. Through 16S rRNA gene sequencing and non-targeted metabolomics analysis, we identified significant differences in the composition and diversity of the gut microbiota between these two species. The gut microbiota of Chinese and Malayan pangolins is dominated by Firmicutes and Proteobacteria at phylum level. At the genus level, the abundance of Clostridium sensu stricto 13 in Chinese pangolins was significantly higher than Malayan pangolins, whereas Peptostreptococcus, and Blautia are more abundant in Malay pangolins. Moreover, integrative analysis of the microbiome and metabolome revealed important correlations: Peptostreptococcus was positively correlated with 13-HpOTrE (r) metabolism, while Clostridium sensu stricto 13 was negatively correlated with 13-HpOTrE (r) metabolism. Blautia was positively correlated with 1-phenylethylamine metabolism. These results provided important gut microbiome and metabolomics data for the conservation and artificial breeding of pangolins, which can help optimize captive pangolins feeding management and health maintenance.